CNS-selective noncompetitive cholinesterase inhibitors derived from the natural piperidine alkaloid (-)-spectaline - Castro, Newton G.; Costa, Rodrigo S.; Pimentel, Luisa S. B.; Danuello, Amanda [UNESP]; Romeiro, Nelilma C.; Viegas, Claudio; Barreiro, Eliezer J.; Fraga, Carlos A. M.; Bolzani, Vanderlan da Silva [UNESP]; Rocha, Monica S. (Elsevier B.V., 2008)
LASSBio-767 [(-)-3-O-acetyl-spectaline] and LASSBio-822 [(-)-3-O-tert-Boc-spectaline] were recently described as cholinesterase inhibitors derived from the natural piperidine alkaloid (-)-spectaline, obtained from the flowers of Senna spectabilis (Fabaccae). We investigated their mechanism of inhibition of acetylcholinesterase and their efficacy in reversing scopolamine-induced amnesia. Competition assays with the substrate acetylthiocholine showed a concentration-dependent reduction in rat brain cholinesterase V-max without changes in apparent K-m. The kinetic data for LASSBio-767 and LASSBio-822 were best fit by a model of simple linear noncompetitive inhibition with K-i of 6.1 mu M and 7.5 mu M, respectively. A dilution assay showed a fast and complete reversal of inhibition, independent of incubation time. Simulated docking of the compounds into the catalytic gorge of Torpedo acetylcholinesterase showed interactions with the peripheral anionic site, but not with the catalytic triad. Anti-amnestic effects in mice were assessed in a step-down passive avoidance test and in the Morris water maze 30 min after injection of scopolamine (1 mg/kg i.p.). Saline, LASSBio-767, or LASSBio-822 was administered 15 min before scopolamine. Both compounds reversed the scopolamine-induced reduction in step-down latency at 0.1 mg/kg i.p. LASSBio-767 reversed scopolamine-induced changes in water maze escape latency at 1 mg/kg i.p. or p.o., while its cholinergic side effects were absent or mild up to 30 mg/kg i.p. (LD50 above 100 mg/kg i.p.). Thus, the (-)-spectaline derivatives are potent cholinergic agents in vivo, with a unique profile combining noncompetitive cholinesterase inhibition and CNS selectivity, with few peripheral side effects. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: acetylcholinesterase; Alzheimer; water maze; passive avoidance; (-)-spectaline; noncompetitive inhibitor